Dinamika Politik Dalam Pendirian Dan Pengelolaan BUMDes: Studi Pada Tiga BUMDes Terbaik Jawa Timur - Juwita Hayyuning Prastiwi; Irma Fitriana Ulfah (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2022)
Research on the best practices of BUMDes establishment and management has practical significance for providing advice to BUMDes practitioners and the government. Academically, the significance of this research is expected to contribute to the development of the concept of good village governance, especially in the aspect of the network between governance actors in the context of the BUMDes. This study aims to describe the political dynamics in the formation and management, as well as identify best practices for the formation and management of BUMDes. This study is important considering that since the enactment of Law no. 6 of 2014, BUMDes placed as a facilitator of village progress and autonomy. To see these dynamics, qualitative research was conducted with informants including government actors in three BUMDes in East Java, namely BUMDes Podho Joyo in Gresik, Makmur Abadi in Pacitan, and Aneka Usaha in Bojonegoro. The results showed the dominant role of the supra-village government in the process of forming the three BUMDes, that is a combination of reactions to central government regulations accompanied by capital and assistance by the local government. In the management aspects, the work of the three BUMDes is relatively able to meet the needs of village community, especially in BUMDes Podho Joyo in Gresik. However, the existence of each BUMDes cannot be separated from the strong control of the BUMDes director. Research on the best practices of BUMDes establishment and management has practical significance for providing advice to BUMDes practitioners and the government. Academically, the significance of this research is expected to contribute to the development of the concept of good village governance, especially in the aspect of the network between governance actors in the context of the BUMDes. This study aims to describe the political dynamics in the formation and management, as well as identify best practices for the formation and management of BUMDes. This study is important considering that since the enactment of Law no. 6 of 2014, BUMDes placed as a facilitator of village progress and autonomy. To see these dynamics, qualitative research was conducted with informants including government actors in three BUMDes in East Java, namely BUMDes Podho Joyo in Gresik, Makmur Abadi in Pacitan, and Aneka Usaha in Bojonegoro. The results showed the dominant role of the supra-village government in the process of forming the three BUMDes, that is a combination of reactions to central government regulations accompanied by capital and assistance by the local government. In the management aspects, the work of the three BUMDes is relatively able to meet the needs of village community, especially in BUMDes Podho Joyo in Gresik. However, the existence of each BUMDes cannot be separated from the strong control of the BUMDes director.